1977
DOI: 10.1002/1097-4679(197707)33:3<662::aid-jclp2270330312>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Judgment of emotion among chronic schizophrenics

Abstract: This study investigated accuracy of judgment as to posed facial expressions and nonverbal scenes of various emotions. Ss were 16 male and 16 female chronic schizophrenics and a normal control group of equal size and sex composition. The results revealed that normal Ss were significantly more accurate than schizophrenics in identifying emotions from both posed photographs of the face and nonverbal videotape scenes. S sex was not found to affect differentially the schizophrenic or normal Ss' response accuracy to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
1
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 9 publications
3
60
1
2
Order By: Relevance
“…Twenty-two studies examined sex differences in FEP in adult samples of chronically ill people with schizophrenia. The majority of these studies (n = 19) did not find sex differences in FEP, either on identification tasks [31][32][33][34][35][36][37][38][39][40][41] , discrimination tasks [42,43] , or in studies that included both task types [44][45][46][47][48][49] . Three studies included in Kohler et al [7] , Chan et al [5] , and Savla et al [9] found sex differences in FEP performance on identification tasks in adults with chronic schizophrenia.…”
Section: Adults With Chronic Schizophreniamentioning
confidence: 99%
“…Twenty-two studies examined sex differences in FEP in adult samples of chronically ill people with schizophrenia. The majority of these studies (n = 19) did not find sex differences in FEP, either on identification tasks [31][32][33][34][35][36][37][38][39][40][41] , discrimination tasks [42,43] , or in studies that included both task types [44][45][46][47][48][49] . Three studies included in Kohler et al [7] , Chan et al [5] , and Savla et al [9] found sex differences in FEP performance on identification tasks in adults with chronic schizophrenia.…”
Section: Adults With Chronic Schizophreniamentioning
confidence: 99%
“…In two previous studies (Dougherty et al, 1974;Muzekari & Bates, 1977), the schizophrenic populations had been hospitalized on their current admission more than 5 years. One study (Muzekari & Bates, 1977) suggested that the deficits in schizophrenic recognition of emotion in faces might be due to long-term hospitalization. The schizophrenic subjects in the present study were selected for a much shorter current hospitalization to assess this issue.…”
Section: Subjectsmentioning
confidence: 99%
“…However, some of these studies also found a specific relationship between affect recognition and positive symptoms such as bizarre behavior (Schneider et al, 1995), thought disorder (Kohler et al, 2000), and overall positive symptoms (Lewis and Garver, 1995). One study reported that combined voice and face affect recognition scores were related to positive and disorganized symptoms but not negative symptoms (Poole et al, 2000), and several groups reported no significant correlations between affect recognition performance and clinical symptoms (Salem et al, 1996;Borod et al, 1993;Muzekari and Bates, 1977;Novic et al, 1984;Wolwer et al, 1996;Addington and Addington, 1998).…”
Section: Introductionmentioning
confidence: 99%